"Go beyond your own comfort zone and challenge yourself": A comparison on the use of physically active learning in Norway, the Netherlands and the UK. (October 2022) - Chalkley, Anna E.; Mandelid, Mathias B.; Thurston, Miranda; Daly-Smith, Andrew; Singh, Amika; Huiberts, Irma; Archbold, Victoria S.J.; Resaland, Geir K.; Tjomsland, Hege E.
Abstract: The adoption of physically active learning (PAL) in schools is becoming more widespread. To understand how PAL is being used in different countries and explore if and how methods and strategies differ, this paper draws cross-national comparisons in primary school teachers' use of PAL. Thirteen focus groups were conducted with 54 teachers from Norway, the Netherlands and the UK. Four themes were identified using thematic analysis: 1) teachers' values and beliefs about PAL; 2) influence of school context; 3) influence of the national policy context and; 4) managing teacher dissonance when using PAL. Use of PAL was related to teachers' values and beliefs and the degree to which these aligned with the context of the school and the wider educational system. The findings underline the importance of addressing teachers' competence, opportunity and agency to use PAL in different contexts.